1998
DOI: 10.1086/597600
|View full text |Cite
|
Sign up to set email alerts
|

Anticapsular Polysaccharide Antibodies and Nasopharyngeal Colonization withStreptococcus pneumoniaein Infant Rats

Abstract: To evaluate the effect of passive immunization with anticapsular antibodies on nasopharyngeal carriage, two models of Streptococcus pneumoniae colonization were developed in infant rats. In a direct inoculation model, 3- to 4-day-old infant rats were intranasally inoculated with 2 x 10(5) cfu of S. pneumoniae type 3 or 6 x 10(3) cfu of S. pneumoniae type 23F. In an intralitter transmission model, 2 infant rats were intranasally inoculated with 10(3) cfu of pneumococcus type 3 or type 19F and placed in a cage c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…Anticapsular Abs not only prevent invasion but, as shown by active and passive immunization (5,24), are sufficient to prevent pneumococcal colonization; however, they may not be neces- WCV͞CT and subsequently treated with rat IgG or anti-CD8 Ab were significantly protected against nasopharyngeal colonization compared with mice that were immunized with CT alone (P Ͻ 0.05 for each comparison) and were indistinguishable from mice that received WCV͞CT with no additional treatment (P Ͼ 0.5). In contrast, mice treated with anti-CD4 Ab were not protected (P ϭ 0.46 vs. CT group) and were significantly more colonized than mice in the three other WCV͞CT immunized groups (P Ͻ 0.05).…”
Section: Discussionmentioning
confidence: 98%
“…Anticapsular Abs not only prevent invasion but, as shown by active and passive immunization (5,24), are sufficient to prevent pneumococcal colonization; however, they may not be neces- WCV͞CT and subsequently treated with rat IgG or anti-CD8 Ab were significantly protected against nasopharyngeal colonization compared with mice that were immunized with CT alone (P Ͻ 0.05 for each comparison) and were indistinguishable from mice that received WCV͞CT with no additional treatment (P Ͼ 0.5). In contrast, mice treated with anti-CD4 Ab were not protected (P ϭ 0.46 vs. CT group) and were significantly more colonized than mice in the three other WCV͞CT immunized groups (P Ͻ 0.05).…”
Section: Discussionmentioning
confidence: 98%
“…Il1r1 ؊/؊ mice do not have altered adaptive immunity to the pneumococcus. Although there is a contribution of type-specific antibody to protection induced by either vaccination or prior exposure (29,30), effective clearance of primary colonization requires Th17-dependent cellular immunity rather than humoral responses (8,31). Il-1␤ is a known driver of Th17 responses (32), which contribute to macrophage recruitment during colonization (8).…”
Section: Weeks After Inoculation There Was a Significantly Higher Bacmentioning
confidence: 99%
“…A role for the capsule in colonization has not been described, and in vitro studies have suggested that it may interfere with this process (1,17,32,42,44,48). The ability of capsule-specific antibodies to reduce carriage, however, suggests that the capsule is expressed during nasopharyngeal colonization (18,34,36). Moreover, the varied ability of encapsulated strains of different serotypes to colonize the nasopharynx suggests some influence of the capsule on colonization (2,14,49,50,56).…”
mentioning
confidence: 99%